2021
DOI: 10.23887/jet.v5i3.35108
|View full text |Cite
|
Sign up to set email alerts
|

Competency of Digital Technology: The Maturity Levels of Teachers and Students in Vocational Education in Indonesia

Abstract: One of the needs for competence in the world of work in the 21st century and the era of the industrial revolution 4.0. is competence in using digital technology. Vocational education is required to provide digital competencies to students through their learning. The maturity level of digital technology competence is divided into five levels, namely caring, literacy, capability, creativity, and being critical of using digital technology. This study aims to analyze the maturity level of vocational education teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 66 publications
0
58
0
5
Order By: Relevance
“…The results of the study which show that the absorption rate of vocational education graduates is still low, especially in the automotive sector is very relevant. Previous research revealed that vocational teachers still have a low level of maturity in using digital technology in learning (Astuti et al, 2021;Mutohhari, Sofyan, et al, 2021). Thus, competencies based on the 21st century and industry 4.0 are difficult to build, so the estuary of current graduate absorption tends to be low.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study which show that the absorption rate of vocational education graduates is still low, especially in the automotive sector is very relevant. Previous research revealed that vocational teachers still have a low level of maturity in using digital technology in learning (Astuti et al, 2021;Mutohhari, Sofyan, et al, 2021). Thus, competencies based on the 21st century and industry 4.0 are difficult to build, so the estuary of current graduate absorption tends to be low.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmed by numerous research findings indicating that online learning can be conducted in a flexible manner and encourages students to engage in independent learning (Richardson et al, 2016;. Lecturers must actively motivate students to adapt to social changes in the field of digital technology and foster a positive learning environment through online instruction (Astuti et al, 2021;Wijaya et al, 2021). Online learning media can be defined as those that are equipped with control devices that enable users to operate and access what they require, such as downloading resources for educational materials (Kristanto et al, 2021;Udayani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At the conclusion of the quiz, this quiz will automatically assess the results of student work, assisting the lecturer in the correction process. From a student's perspective, the cause is that students have not yet engaged in maximal learning activities due to a deficiency in critical thinking (Astuti et al, 2021;Purwitaningrum & Prahmana, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students are deeply aware of the changes brought over by digital technologies, by their impact on the learning process. Using this type of educational technology in elementary, junior, and high school education in Indonesia, on the one hand, is a new practice that makes certain requirements for the material, technical, organizational, and professional attainment level of information technology (Astuti et al, 2021;Bastemur & Bastemur, 2015). On the other hand, the school community does not have the necessary competencies and range of tools to implement and use distance learning technologies.…”
Section: Introductionmentioning
confidence: 99%